Automation Inner Speech as an Anthropomorphic Feature Affecting Human Trust: Current Issues and Future Directions - Geraci, Alessandro; D'Amico, Antonella; Pipitone, Arianna; Seidita, Valeria; Chella, Antonio (Frontiers in Robotics and AI, 2021)
This paper aims to discuss the possible role of inner speech in influencing trust in human–automation interaction. Inner speech is an everyday covert inner monolog or dialog with oneself, which is essential for human psychological life and functioning as it is linked to self-regulation and self-awareness. Recently, in the field of machine consciousness, computational models using different forms of robot speech have been developed that make it possible to implement inner speech in robots. As is discussed, robot inner speech could be a new feature affecting human trust by increasing robot transparency and anthropomorphism.